Designing a Simulation Model for Organizational Agility Development in Hospitals of Ardabil Province, Iran - Hossein Rahimi Klour; Seyed Ali Naghavi (Tehran University of Medical Sciences, 2023)
Background and objective: As a critical factor for hospital effectiveness, agility uncovers the way such organizations react to internal and external changes. From this perspective, the present study was to design an agent-based model to simulate organizational agility development in the hospitals of Ardabil Province, Iran, in view of the effective factors. Materials & Methods: Utilizing an exploratory, mixed-methods research design, this study was performed in accordance with inductive-deductive reasoning. For this purpose, the samples included 10 theoretical and experimental experts, selected by purposive sampling of the non-probability type. As well, the data collection tools were interviews and questionnaires. During the qualitative phase, the main factors affecting organizational agility were initially isolated using thematic analysis. Afterward, the given factors were prioritized with the fuzzy Delphi method in the quantitative phase. Ultimately, the model for organizational agility development was simulated through the agent-based approach. Results: With reference to the study results, 50 primary codes, 15 sub-themes, and 5 main themes were identified, and then "influence in management" was acknowledged as the most significant one shaping organizational agility. Besides, the simulation outputs demonstrated that the proposed model could provide the right estimate of the future of organizational agility development in the hospitals of Ardabil Province, Iran. Conclusion: Along with the study results, hospital managers are suggested to reflect on the effective factors identified here to better fulfill organizational agility development.